Quality control initiative on the evaluation of the dysmegakaryopoiesis in myeloid neoplasms: Difficulties in the assessment of dysplasia - Goasguen, Jean E.; Bennett, John M.; Bain, Barbara J.; Brunning, Richard D.; Vallespí, Maria-Teresa; Tomonaga, Masao; Zini, Gina; Renault, Alain (Leukemia research, 2016)
•The presence of micromegakaryocytes correlates strongly with myeloid neoplasia.•Micromegakaryocytes can be identified reliably.•Multinucleated megakaryocytes are not specific for myeloid neoplasia.•Cytoplasmic dysplasia is not useful in recognising MDS.•‘Possibly dysplastic’ cells should be excluded from counts in suspected MDS. Evaluation of megakaryocyte morphology is difficult but can be essential for the diagnosis of myelodysplastic syndromes (MDS) and other myeloid neoplasms. We agreed upon descriptions and provided images of megakaryoblasts and of normal and dysplastic megakaryocytes, which were used as a basis for assessing the concordance of expert morphologists in their recognition. We showed a high rate of concordance for the recognition of micromegakaryocytes and confirmed their strong association with hematologic neoplasia, including MDS. Concordance was also found to be good for the recognition of multinucleated megakaryocytes, which showed a significant association with MDS. However cytoplasmic abnormalities were found not to be useful in MDS recognition. The occurrence of appreciable numbers of nonlobulated and hypolobulated megakaryocytes in individuals without a myeloid neoplasm was confirmed. We demonstrated that subjects without a myeloid neoplasm can have some megakaryocytes that are assessed as ‘dysplastic’ or ‘possibly dysplastic’ and that to avoid over diagnosis of dysplasia, ‘possibly dysplastic’ forms should be excluded from the count of dysplastic cells. Our results demonstrate that the nature as well as the presence of megakaryocyte dysplasia is important in the diagnosis of MDS; although evaluation of 30 megakaryocytes is strongly recommended, it may be possible to recognize diagnostically important dysplasia when fewer megakaryocytes are present but highly diagnostic forms are seen.